La didattica del collettivo e il Poema pedagogico - Vincenzo Orsomarso (Firenze University Press, 2011)
The author makes a careful and thorough consideration of Pedagogical Poem edition edited by Nicola Siciliani de Cumis. It is an edition that comes after other studies related Makarenco and Russian education and the work completes a careful and sophisticated itinerary of studies.